Algerian Economic Diplomacy in the Context of the Global Trade War: Integrating SWOT and Task Force Strategies to Strengthen Its African Positioning - Tebra, Mokaddem (Journal of Ecohumanism, 2025)
This study aims to analyze the qualitative transformation of Algerian economic diplomacy amid the intensifying global trade war and its profound geo-economic challenges. The world is experiencing a redefinition of economic power balances, compelling Algeria, as a rising regional power, to reconstruct its diplomatic tools on more flexible and forward-looking foundations. The central premise of this research is that the integration of SWOT analysis and Task Force methodology constitutes a practical approach for restructuring Algerian economic diplomacy, transforming it from a traditional model into a strategic mechanism capable of responding effectively to major continental changes. Our analysis demonstrates that SWOT facilitates the identification of strengths (geographical location, natural resources, African reach), weaknesses (logistical infrastructure gaps, delayed financial reforms), opportunities (AfCFTA momentum), and threats (geopolitical instability and trade wars). Task Force methodology complements SWOT by translating diagnostic insights into actionable economic and diplomatic initiatives, ensuring coherent and targeted execution. The research confirms that Algeria, through economic diversification and strategic foresight, is capable of converting current global challenges into sustainable opportunities, asserting a proactive and ethical role in Africa. The study concludes that smart economic diplomacy based on analysis, institutional coordination, and operational effectiveness is essential for building a competitive and resilient national economy.